Efficacy and safety of ferric carboxymaltose infusion in reducing anemia in patients receiving chemotherapy for nonmyeloid malignancies: A randomized, placebo‐controlled study (IRON‐CLAD). Issue 12 (19th November 2021) - Makharadze, Tamta; Boccia, Ralph; Krupa, Anna; Blackman, Nicole; Henry, David H.; Gilreath, Jeffrey A.
Abstract: Erythropoiesis‐stimulating agents (ESA) are effective for chemotherapy‐induced anemia (CIA) but associated with serious adverse events. Safer alternatives would be beneficial in this population. The efficacy and safety of ferric carboxymaltose (FCM) as monotherapy for CIA was evaluated. This Phase 3, 18‐week, double‐blind, placebo‐controlled study randomized adults with ≥ 4 weeks of chemotherapy remaining for treatment of nonmyeloid malignancies with CIA to FCM (two 15 mg/kg infusions 7 days apart; maximum dose, 750 mg single/1500 mg total) or placebo. The primary efficacy endpoint was percentage of patients with decreases in hemoglobin (Hb) ≥ 0.5 g/dL from weeks 3 to 18; the key secondary efficacy endpoint was change in Hb from baseline to week 18. Inclusion criteria included: (Hb) 8–11 g/dL, ferritin 100–800 ng/mL, and transferrin saturation (TSAT) ≤35%. In 244 patients ( n = 122, both groups), the percent of patients who maintained Hb within 0.5 g/dL of baseline from weeks 3 to 18 was significantly higher with FCM versus placebo (50.8% vs. 35.3%; p = 0.01). Mean change in Hb from baseline to week 18 was similar between FCM and placebo (1.04 vs. 0.87 g/dL) but significantly greater with FCM with baseline Hb ≤ 9.9 g/dL (1.08 vs. 0.42 g/dL; p = 0.01). The percent with ≥ 1 g/dL increase from baseline was significantly higher with FCM versus placebo (71% vs. 54%; p = 0.01), occurring in a median 43 versus 85 days ( p = 0.001). Common adverse events in the FCM arm included neutropenia (17%), hypophosphatemia (16%), and fatigue (15%). FCM monotherapy effectively maintained Hb and was well tolerated in CIA.